Kepuasan Pelanggan Di Bumi Sunda Resto Bandung - Sakti Wibawa, Idham; Nursyashinta Adel, Eka (Akademi Pariwisata NHI Bandung, 2024)
Customer satisfaction is an important aspect, especially in the restaurant world, because ensuring customers are satisfied can keep the business running and increase revenue, but in practice customer satisfaction is a point that is rarely measured for one reason or another. The purpose of this research is to determine the level of guest satisfaction at Bumi Sunda Resto. The method used in this research is a descriptive method, namely a method that thoroughly describes what happens at the research locus. A total of 43 samples were taken using the Slovin formula. The results of this research showed that the condition of guest satisfaction at Bumi Sunda Resto was stated to be dissatisfied. Keywords: Satisfaction, Custome, Restaurant